Epigenetic Inheritance and the Intergenerational Transfer of Experience. [article]. - Harper, Lawrence V.
Currently, behavioral development is thought to result from the interplay among genetic inheritance, congenital characteristics, cultural contexts, and parental practices as they directly impact the individual. Evolutionary ecology points to another contributor, epigenetic inheritance, the transmission to offspring of parental phenotypic responses to environmental challenges-even when the young do not experience the challenges themselves. Genetic inheritance is not altered, gene expression is. Organismic pathways for such transmission exist. Maternal stress the latter half of a daughter's gestation may affect not only the daughter's but also grand-offspring's physical growth. The authors argues that temperamental variation may be influenced in the same way. Implications for theory and research design are presented along with testable predictions. -- [from the author] -- ( from the author).
Keywords: Psychology-Periodicals.; Epigenetic inheritance; Temperament; Socialization; Maternal inheritance